Intentional replantation: case report - Duque-Urióstegui, Cristhal; Alvarez Hernández, Luis A.; Muñoz-Ramírez, Yanirethe I.; Vallejo Ochoa, Verónica; Méndez Hernández, Noemí; González Madó, Karen I.; Poceros Angeles, Emmanuel; Briseño Flores, Carlos; Duque-Urióstegui, Carla B.; Corona Maya, Alicia M.; Castañeda-Palacios, Gabriela; Barrera-Mera, Baltazar; et al. (International Journal of Research in Medical Sciences, 2021)
Intentional reimplantation is a procedure in which an intentional tooth extraction is performed followed by reinsertion of the extracted tooth. We present the case of a 50-year-old male patient who came to the consultation due to incrustation detachment in tooth #37, when performing the radiographic study an extensive apical lesion was observed in tooth #36 with a sinuous path and the presence of purulent exudate. The tooth #36 was extracted, apicoectomy, retro preparation and retrograde filling were carried out for later reimplantation, showing bone regeneration after one year of evolution.